The Fall of Man: Thematic Survey on Professional Ethics and Integrity in M.M. Mabuza’s Nyuku wa Mbyana (Journal of Pharmaceutical Negative Results, 2022)
Mabuza’s text presents an engrossingly hooking departure for a make-belief textual display of matters arising in the 'concrete' world. The paper is an attempt to unearth some of the acts exhibited by, especially, professionals, in their narcissist desires and adventures to attain gains, regardless of the means – unconsciously engulfed in ‘the result justifies the means’ propensity. Corrupt wiggles personified by dramatic key players, Diza and Xiphongo shamelessly and hardheartedly dominate the creative sphere, by creating a huge watershed for corruption and such related anomalies. Through official power manipulation and abuse. This paper addressed some of the anomalies akin to professionals and top post-holders as presented in the said text.